The Expandables: Cracking the Staphylococcal Cell Wall for Expansion Microscopy - Kunz, Tobias C.; Rühling, Marcel; Moldovan, Adriana; Paprotka, Kerstin; Kozjak-Pavlovic, Vera; Rudel, Thomas; Fraunholz, Martin (Frontiers in Cellular and Infection Microbiology, 2021)
Expansion Microscopy (ExM) is a novel tool improving the resolution of fluorescence microscopy by linking the sample into a hydrogel that gets physically expanded in water. Previously, we have used ExM to visualize the intracellular Gram-negative pathogens Chlamydia trachomatis, Simkania negevensis, and Neisseria gonorrhoeae. Gram-positive bacteria have a rigid and thick cell wall that impedes classic expansion strategies. Here we developed an approach, which included a series of enzymatic treatments resulting in isotropic 4× expansion of the Gram-positive pathogen Staphylococcus aureus. We further demonstrate the suitability of the technique for imaging of planktonic bacteria as well as endocytosed, intracellular bacteria at a spatial resolution of approximately 60 nm with conventional confocal laser scanning microscopy.